Cytokine responses of peripheral blood mononuclear cells to allergen do not identify asthma or asthma phenotypes. Issue 11 (24th October 2013) - Simms, E.; Kjarsgaard, M.; Denis, S.; Hargreave, F. E.; Nair, P.; Larché, M.
Summary: Background: Asthmatic patients are often differentiated based on their atopic status (atopic or nonatopic) and type of bronchitis (eosinophilic, neutrophilic, both, or neither). There is evidence supporting a central role for the T cell in asthma, but the role of allergen‐induced T cell cytokines in driving disease in different asthma phenotypes remains unclear. Objective: To investigate the hypothesis that peripheral blood mononuclear cells (PBMCs) from asthma patients with different phenotypes would react characteristically to a panel of common aeroallergens. Methods: We incubated PBMCs from 41 asthma patients and 8 healthy controls with allergen and assessed PBMC proliferation by 3 H‐thymidine incorporation and the production of the cytokines IL‐5, IL‐17A, IL‐23, IL‐10, and IFN‐γ by ELISA. Results: No differences in PBMC proliferation or cytokine production were found in patients with asthma, compared with healthy controls, or between patients with different asthma phenotypes. Conclusions and Clinical Relevance: Peripheral blood mononuclear cell cytokine responses to allergen are not able to assist in the discrimination between disease state, atopic status, or type of bronchitis in asthma.